2010 International Conference on P2P, Parallel, Grid, Cloud and Internet Computing 2010
DOI: 10.1109/3pgcic.2010.73
|View full text |Cite
|
Sign up to set email alerts
|

A Volunteer Classification Method for Disaster Recovery

Abstract: In recent years, there are many volunteer activities for disaster recovery and many people are participating as volunteers. However, the number of volunteers which make troubles (trouble-making volunteers) is increasing, which a big problem in Japan. In order to deal with this problem, we propose a volunteer classification method for disaster recovery to support an effective selection of volunteers and eliminate "trouble making volunteers". In this paper, we introduce the concept of disaster information design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Different researchers have proposed matching algorithm based on various situation with volunteer such as OWL-S matcher, RF-based localization techniques, Web2.0 style, sizespecified community creation method and classification method (Hong et al 2007;Lo et al 2010;McCann et al 2008;Shen and Doan 2008;Yu et al 2012;Endo and Sugita 2010;Chen et al 2011). Based on our review, we found that there is the various matching technique used in existing volunteering system.…”
Section: Recruitment and Selection For Volunteersmentioning
confidence: 98%
“…Different researchers have proposed matching algorithm based on various situation with volunteer such as OWL-S matcher, RF-based localization techniques, Web2.0 style, sizespecified community creation method and classification method (Hong et al 2007;Lo et al 2010;McCann et al 2008;Shen and Doan 2008;Yu et al 2012;Endo and Sugita 2010;Chen et al 2011). Based on our review, we found that there is the various matching technique used in existing volunteering system.…”
Section: Recruitment and Selection For Volunteersmentioning
confidence: 98%
“…Besides that, matching technique is an important part of recruitment and selection of volunteer because to find the suitable volunteer before assigning the task. Different researchers have proposed matching algorithm based on various situation with volunteer such as OWL-S matcher, RF-based localization techniques, Web2.0 style, size-specified community creation method and classification method ( [17], [18], [19], [20], [21], [7]). Based on our review, we found that there is the various matching technique used in existing volunteering system.…”
Section: Recruitment and Selection For Volunteersmentioning
confidence: 99%